Hubungan Koordinasi Mata-Kaki dengan Ketepatan Passing Sepakbola Dengan kaki Bagian Dalam Pada Siswa SMA Mutiara Bangsa - Akhmady, Alief Lam (Peneliti.net, 2024)
This study aims to determine the relationship between eye-foot coordination and the accuracy of football passing with the inside of the foot in students of Mutiara Bangsa High School. This study is a correlational study. The subjects of this study were 30 male students of Mutiara Bangsa High School. The results of the study showed that the results of the data analysis obtained a calculated r value of 0.801> r table value of 0.361, with a significance value of 0.05, so there is a relationship between eye-foot coordination and the accuracy of football passing with the inside of the foot in students of Mutiara Bangsa High School. the conclusion of this study is that there is a relationship between eye-foot coordination and the ability to pass football with the inside of the foot in students of Mutiara Bangsa High School.